Cocoa [sic] Palms, Trinidad - (:unkn) unknown (My University, 2009)
A picture of a man on horseback on a beach lined by tall coconut trees.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coconut palm--Trinidad and Tobago; Coconut industry--Trinidad and Tobago; Agriculture--Trinidad and Tobago